Os processos homeostáticos do cálcio diferem entre espécies de animais domésticos: Um breve panorama - Vargas, Julián A.C. [UNESP] (My University, 2017)
There is a lack of knowledge regarding differences of calcium homeostatic mechanisms between domestic animal species, so they are often generalized to all species. Thus, the present literature review pretends to present a brief overview about differences in the calcium homeostatic mechanisms among some species of domestic animals. In the case of terrestrial animals, calcium required is obtained mainly from feed, and its greatest absorption occurs in the duodenum. Calcium can be transported in two ways, which depends on species: transport between cells and transport through cells. Other aspect commonly generalized between species are the hormonal and physiological mechanisms that regulate plasma calcium concentration. Young dogs are more susceptible to hypocalcemia than mature dogs. In birds, calcitonin (CT) concentration may be higher than in mammals, which makes birds less susceptible to develop hypercalcemia. Unlike other mammalian species, calcium concentration in the blood of rabbits reflects the calcium ingested from the diet, which is produced by a lower secretion of CT than in other mammalian species. Several studies present evidence that goats produce more calcitriol than sheep and, therefore, goats have a greater ability to maintain a constant calcium concentration when calcium dietary is restricted. Thus, in the present review is showed there are differences in calcium homeostasis and metabolism between domestic animal species. Therefore, the characterization of calcium regulatory processes in animal species may contribute to their more accurate estimation of calcium nutritional requirements, which may result in the maximization of animal production, and in the reduction of diseases caused by calcium deficiency or excess.
Homeostatic calcium processes differ among domestic animal species: A brief overview
Keywords: Absorption; Animal; Hormones; Mineral; Regulation